ANALISIS PERKEMBANGAN USAHA MIKRO KECIL MENENGAH SEBELUM DAN SESUDAH MENERIMA PEMBIAYAAN SYARIAH (STUDI PADA PT. BPRS HIKMAH WAKILAH BANDA ACEH) - Tri Irawan, Febrian; Mulyany, Ratna (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This study aims to examine whether there is an improvement in the profit, the number of customers, and the number of employees for Micro, Small and Medium Enterprises (MSMEs) before and after receiving shariah financing. Total of 93 respondents were selected based on purposive sampling method with a focus on MSMEs which have received shariah financing from PT. BPRS Hikmah Wakilah Banda Aceh. This research is quantitative descriptive using questionnaires to obtain data about the development of MSMEs. Data was analyzed using the Wilcoxon sign rank test. This study found there is a difference and an increase in the profit based on the test of descriptive statistic and Wilcoxon rank test. Likewise with the aspects of customers and employees, this study discovered that there is a difference and an increase in the number of customers and employees pursuant to the receip of shariah financing by the MSMEs. It implies that sharia financing plays a role in the development of MSMEs.